Risks Facing a Pregnant Teen in Iraq, the Health Problems, and the Proposed Solutions - Zainab Abdul Ameer Jaafar; Reshed Obeid; Dina Salman (AlQalam Journal of Medical and Applied Sciences, 2024)
Teenage pregnancy continues to be a major health and social problem in various parts of the world including Iraq. A case control study conducted over 2 years in the department of obstetrics and gynecology, Al-Yarmouk tertiary hospital in Baghdad. Two-hundred primigravida were chosen according to strict inclusion and exclusion criteria, the case group were 100 late teenagers (16 y-19 y) and the control group were 100 women aged between 26-29 y. The women in both groups were attending labor ward, clinical and laboratory evaluation was performed, and women were followed during labor. The mode of delivery and neonatal outcome were all recorded. In comparison to the adult women group, teenage mothers have lack of antenatal care and less use of supplements (P<0.0001), lower iron indices particularly serum iron and serum ferritin (P<0.0001). In addition, there was a higher incidence of Caesarean section (P=0.0326), postpartum hemorrhage (P=0.046). Neonates of younger mothers were more likely to be preterm (P<0.0001), have low birth weight (P<0.0009), intrauterine growth restriction (P=0.005) with higher neonatal mortality (P=0.017). Teenage mothers have higher antepartum, intrapartum, and postpartum complications in addition to poor neonatal outcomes in comparison to their older peers. It is crucial to spread awareness and knowledge about these risks to reduce the still high incidence of pregnancy among this group of population. Moreover, young mothers should be advised about the importance of antenatal care attendance, good nutrition, and the use of supplements during pregnancy to enhance health both for mothers and their offspring. لا يزال حمل المراهقات يمثل مشكلة صحية واجتماعية كبيرة في أجزاء مختلفة من العالم بما في ذلك العراق. دراسة حالة ومراقبة أجريت على مدار عامين في قسم أمراض النساء والتوليد في مستشفى اليرموك التخصصي في بغداد. تم اختيار مائتي خديجة وفقًا لمعايير التضمين والاستبعاد الصارمة، وكانت مجموعة الحالة 100 مراهق متأخر (16 سنة - 19 سنة) وكانت المجموعة الضابطة 100 امرأة تتراوح أعمارهن بين 26-29 سنة. كانت النساء في كلا المجموعتين يحضرن جناح المخاض، وتم إجراء التقييم السريري والمختبري، وتمت متابعة النساء أثناء المخاض. تم تسجيل جميع طريقة الولادة ونتائج حديثي الولادة. بالمقارنة مع مجموعة النساء البالغات، تعاني الأمهات المراهقات من نقص الرعاية السابقة للولادة واستخدام أقل للمكملات الغذائية (P <0.0001)، وانخفاض مؤشرات الحديد وخاصة حديد المصل وفيريتين المصل (P <0.0001). وبالإضافة إلى ذلك، كان هناك ارتفاع في حدوث العمليات القيصرية (P = 0.0326)، ونزيف ما بعد الولادة (P = 0.046). كان الولدان من الأمهات الأصغر سناً أكثر عرضة للخداج (P <0.0001)، وانخفاض الوزن عند الولادة (P <0.0009)، وتقييد النمو داخل الرحم (P = 0.005) مع ارتفاع معدل وفيات الولدان (P = 0.017). تعاني الأمهات المراهقات من مضاعفات أعلى قبل الولادة وأثناءها وبعدها بالإضافة إلى نتائج ضعيفة عند حديثي الولادة مقارنة بأقرانهن الأكبر سناً. ومن الأهمية بمكان نشر الوعي والمعرفة حول هذه المخاطر للحد من معدلات الحمل التي لا تزال مرتفعة بين هذه المجموعة من السكان. علاوة على ذلك، ينبغي توعية الأمهات الشابات بأهمية حضور الرعاية السابقة للولادة، والتغذية الجيدة، واستخدام المكملات الغذائية أثناء الحمل لتعزيز صحة الأمهات وذرياتهن.